Experimental Study Of The Performance Of A 5-Bladed Horizontal Axis Wind Turbine Of NACA 4415 Profile Using Winglets With Winglet Height Variation - Mustofa, Rida; Sahid, Sahid; Adiprimaswara, Michael Putra Narendra; Aukad, Muhamad; Pratiwi, Okta Ayu; Sulistyoningtyas, Dian Lestari (Eksergi, 2024)
Horizontal axis wind turbine is one type ofturbine used to convert wind energy into mechanical energy. Thepurpose of this research is to design, manufacture, test andanalyze the performance of horizontal shaft wind turbine NACA4415 airfoil blades that do not use winglets with those that usewinglet height variations. The stages of this research includepreparation of literature search, planning and making NACA4415 airfoil blades both using winglets and not using winglets,assembling test equipment and assembling wind turbineinstallations, testing and taking wind turbine performance data,data processing and analysis, final results. The turbine diameterused is 1.1m with a blade thickness of 18 mm and a chord lengthof 38mm. Tests were carried out with winglet height testvariables of 5%, 7%, 9%, and 11% of the rotor length at windspeeds of 4 m/s, 6 m/s, 8 m/s and 10 m/s. The test results showthat the NACA 4415 airfoil horizontal shaft wind turbine usinga winglet with a height of 7% has optimum performance at 4 m/sand 6 m/s with efficiencies of 23.68% and 8.75%, respectively,while when the wind speed is 8 m/s and 10 m/s the optimumturbine performance is achieved when using a 9% winglet withefficiencies of 6.12% and 3.64%, respectively. The mostoptimum turbine performance improvement is achieved whenusing a 7% winglet with an efficiency increase of 204.76% at awind speed test of 4 m/s. Keywords”” HAWT,